Detection and monitoring of Thrips meridionalis (Priesner, 1926) (Thysanoptera: Thripidae) with the colored sticky traps - Aydin, Gökhan; Šlachta, Martin; Karaca, Ismail (Entomological Society Turkey, Ege University, 2020)
This study was conducted to determine the capture rates of Thrips meridionalis (Priesner, 1926) (Thysanoptera:Thripidae) adults on different colored traps between 2017 and 2019 in Isparta Province of Turkey. Three locations were selected for investigation: (1) various orchards with apple trees, (2) various orchards with cherry trees, and (3) various orchards with walnut. The active period of the insect was determined to be between 15 March and 1 April over the three years. Ghost-white traps captured the most T. meridionalis and the differences between this color trap and other colored traps were found significantly differed according to a Tukey’s HSD test in all orchards and in all years (P <0.001). It is suggested that an important technique in integrated pest management for monitoring and controlling of T.meridionalis adults could be to use ghost-white sticky traps.
Keywords: Apple; cherry; colored traps; peach thrips; walnut